1998
DOI: 10.1042/bj3290121
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the roles of mitogen-activated protein kinase kinase and phosphatidylinositol 3-kinase signal transduction in neutrophil effector function

Abstract: Although it is known that many stimuli can activate mitogen-activated protein kinases (MAPKs) and phosphatidylinositol 3-kinases (PI3K) in human neutrophils, little is known concerning either the mechanisms or function of this activation. We have utilized a selective inhibitor of MAPK kinase (MEK), PD098059, and two inhibitors of PI3K, wortmannin and LY294002, to investigate the roles of these kinases in the regulation of neutrophil effector functions. Granulocyte/macrophage colony-stimulating factor, platelet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
128
2
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(143 citation statements)
references
References 67 publications
12
128
2
1
Order By: Relevance
“…However, the signal transduction events upstream to ERK occurring in neutrophils in response to fMLP have been incompletely delineated. Based on immunoblot analysis with anti-phosphop44/42 MAPK antibodies, we found that exposure of neutrophils to fMLP rapidly induced the activation of ERK, reconcile the earlier reports [14,15], and these responses were attenuated by 0.3 WM U0126 ( Fig. 1) as well as 3 WM PD98059 (data not shown), both selective MEK inhibitors [16,17].…”
Section: Phosphorylation Of Erk Via a G Protein-dependent Andsupporting
confidence: 89%
“…However, the signal transduction events upstream to ERK occurring in neutrophils in response to fMLP have been incompletely delineated. Based on immunoblot analysis with anti-phosphop44/42 MAPK antibodies, we found that exposure of neutrophils to fMLP rapidly induced the activation of ERK, reconcile the earlier reports [14,15], and these responses were attenuated by 0.3 WM U0126 ( Fig. 1) as well as 3 WM PD98059 (data not shown), both selective MEK inhibitors [16,17].…”
Section: Phosphorylation Of Erk Via a G Protein-dependent Andsupporting
confidence: 89%
“…Concentration-and temporal-dependent, PD98059-sensitive, fMLP-induced enzymic product formation was readily detected (Figure 2). The p42\p44 MAPK activation by fMLP closely matched that observed in primary isolated human granulocytes using classical kinase assays or Western-blot analysis [11]. Thus PACE is a specific and sensitive method for detection of p42\p44 MAPK phosphoryl- ation in both adherent and suspension cells.…”
Section: Pace Is Useful For Primary Isolated Suspension Cellssupporting
confidence: 68%
“…Blood was obtained from healthy volunteers. Mixed granulocytes were isolated as described earlier [11].…”
Section: Materials and Cell Culturementioning
confidence: 99%
“…However, IL-3 been shown to be activated by IL-3/IL-5/GM-CSF in multifails to activate SEK-1 in FDC-P2 cells [108]. Downstream ple primary cellular lineages and cell lines [22,[86][87][88][89][90].…”
Section: Activation Of Multiplementioning
confidence: 99%
“…Indeed, IL-3/IL-5/GMand DSE-dependent transcription induced by IL-5 [106]. CSF cytokines rapidly induce activation of Ras [22, [89][90][91][92][93] Blocking JNK/SAPK activation with a serine/threonine/tyand c-Raf [22, [94][95][96]. Activation of this pathway will evenrosine phosphatase suggests that this pathway contributes to tually result in enhanced transcription of c-fos and c-jun IL-3-dependent growth but not survival [111].…”
Section: Activation Of Multiplementioning
confidence: 99%